Pengaruh Kompensasi, Iklim Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Cahaya Kawi Ultra Polyintraco Medan - Selva Dani (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
This study aims to determine the effect of compensation, organizational climate and work environment simultaneously on employee performance at PT. Cahaya Kawi Ultra Polyintraco Medan. The total population in this study was 118 people, and by using the saturated sampling technique, a sample of 118 people was obtained. The analysis technique used is multiple linear Regression. The results showed that compensation has a significant effect on employee performance at PT Cahaya Kawi Ultra Polyntraco Medan. Organizational climate has a significant effect on employee performance at PT Cahaya Kawi Ultra Polyntraco Medan. The work environment has a significant effect on employee performance at PT Cahaya Kawi Ultra Polyntraco Medan. Compensation, organizational climate and work environment have a significant effect on employee performance at PT Cahaya Kawi Ultra Polyntraco Medan.